Penny Dreadful and Adaptation Reanimating and Transforming the Monster - Grossman, Julie; Scheibel, Will. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Penny Dreadful and Adaptation is a brilliantly curated collection of essays responding to a brilliantly curated collection of media monsters. Julie Grossman and Will Scheibel have summoned an array of expert contributors as our guides to the liminal Demimonde: chapters range across Victorian, cosmopolitan and Sadean gothics, 'quality' TV as a kind of dialogue with fandom, and Penny Dreadful's own spin-off progeny. Posing new questions about adaptation and its uncanny/medial qualities, this volume will inspire its very own aca-fans and dedicated Dreadfuls alike. Professor Matt Hills, author of Fan Cultures and The Pleasures of Horror Drawing on a wide range of contexts, methods and traditions of representation, Penny Dreadful and Adaptation is endlessly insightful and nuanced. Through the breadth of approaches adopted, this volume's contributors investigate the unbounded textuality of Showtime's landmark television series but also, through this, shed vital new light on the long traditions of retelling that are at the heart of Gothic and horrific cultural forms and their contemporary cultural manifestations. Kate Egan, Senior Lecturer in Film and Media, Northumbria University, UK. This edited collection is the first book-length critical study of the Showtime-Sky Atlantic television series Penny Dreadful (2014-2016), which also includes an analysis of Showtime's 2020 spin-off City of Angels. Chapters examine the status of the series as a work of twenty-first-century cable television, contemporary Gothic-horror, and intermedial adaptation, spanning sources as diverse as eighteenth and nineteenth-century British fiction and poetry, American dime novels, theatrical performance, Hollywood movies, and fan practices. Featuring iconic monsters such as Dr. Frankenstein and his Creature, the "bride" of Frankenstein, Dracula, the werewolf, Dorian Gray, and Dr. Jekyll, Penny Dreadful is a mash-up of familiar texts and new Gothic figures such as spiritualist Vanessa Ives, played by the magnetic Eva Green. Julie Grossman is a professor of English and Communication and Film Studies at Le Moyne College in Syracuse, NY, USA. Will Scheibel is an Associate Professor of English at Syracuse University, USA, where he teaches film and screen studies. .
1. Introduction -- 2. The Medium Is the Model -- 3. The Adaptive Marketing of Penny Dreadful: Listening to the Dreadfuls -- 4. Penny Dreadful and Frankensteinian Collection: Museums, Anthologies, and Other Monstrous Media from Shelley to Showtime -- 5. In the House of the Night Creatures: Penny Dreadful's Dracula -- 6. Vampirism, Blood, and Memory in Penny Dreadful and Only Lovers Left Alive -- 7. 'The Dead Place': Cosmopolitan Gothic in Penny Dreadful's London -- 8. Adapting the Universal Classic Monsters in Penny Dreadful: An Uncanny Resurrection -- 9. Penny Dreadful and the Stage: Lessons in Horror and Heritage -- 10. Ethan Chandler, Penny Dreadful, and the Dime Novel; or, Dancing with American Werewolves in London -- 11. Dreadful Noir, Adaptation, and City of Angels: 'Monsters, All, Are We Not?' -- 12. Penny Dreadful's Palimpsestuous Bride of Frankenstein -- 13. Predators Far and Near: The Sadean Gothic in Penny Dreadful -- 14. 'All Those Sacred Midnight Things': Queer Authorship, Veiled Desire, and Divine Transgression in Penny Dreadful -- 15. Borderland Identities in Penny Dreadful: City of Angels: Urban Planning and Its Impact on Chicano Communities.
Keywords: Adaptation (Literary, artistic, etc.).; Television broadcasting; Goth culture (Subculture).; Adaptation Studies; Television Studies; Gothic Studies